POTENCY OF EEL Anguilla marmorata in NORTH LOMBOK REGENCY, WEST NUSA TENGGARA PROVINCE - Setyono, Bagus Dwi Hari; Junaidi, Muhammad; Marzuki, Muhammad; Paryono, Paryono; Azhar, Fariq (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2018)
Anguilla spp. is one of the ﬁshery commodities that have high economic value. North Lombok regency is one of the central part of Indonesia which is suspected to have potential as an eel migration route. This study aims to obtain information about the identiﬁcation of Anguilla spp ﬁsh populations. in North Lombok Regency. The results showed that the waters area of North Lombok Regency has the potential of eel ﬁsh source Anguilla marmorata. The timing of eel migration is still unknown, so further research is needed which will cover a full year.